GE_GERICHTE C/12139/2013 vom 8. April 2016 - GE Cour de justice (2016)
LÉGITIMATION ACTIVE ET PASSIVE; ACTION EN NULLITÉ(DROIT DES SUCCESSIONS); SUBSTITUTION FIDÉICOMMISSAIRE | CC.488.1; CC.522.1; CC.533.3